Believe in the god who believes in you - Schuller, Robert Harold ([S.l.] : Orient Paperbacks, 1997)
Let the world's premier positive thinker, Robert H. Schuller, help you create a positive mental image of yourself and the God who believes in you! He will show you the God of love who offers what no other force--or source--can: a solid foundation for a healthy, humble pride. And if you thought the Ten Commandments were merely a set of negative, old-fashioned rules, think again! Dr. Schuller has found them to be timeless, positive prescriptions for a renewed sense of self-worth that will help you live life to the fullest.